Grau de cisão de cadeia na degradação termomecânica de polímeros sob multiplas extrusões - Coaquira, Carlos Alberto Cáceres (Universidade Federal de São Carlos, 2004)
One of the ways to follow the polymer degradation has been to calculate the average number of chain scissions (ns) that occurred during its thermomechanical history. The average can be extended for each molecular weight fraction of the original molecular weight distribution curve, which can be done by the Chain Scission Distribution Function (CSDF curve). To calculate CSDF curve originally a correlation rule called Intensity Method was established. In this work another correlation rule was developed to calculate CSDF curve which is called here Concentration Method. Both methods were compared theoretically using an approximation of the MWD curves to a Gaussian shape and experimentally using polypropylene samples that have been subjected to thermomechanical degradation under multiple extrusions. We consider the Concentration Method the proper way to represent the correlation rule because it shows a true agreement with the conventional average ns value. It also presents lower data scattering and can be used as another tool in understanding the polymer degradation field. In order to test this new method it was applied to follow the thermomechanical degradation under multiple extrusions of polypropylene and polystyrene. Polypropylene show a degradation that is mainly a random process (CSDF curve with slop ≅ 0) in the range of low molecular weight up to a critical value Log(MW) ≅ 5.0 and above that it becomes dependent of the MW, called here a preferential process (CSDF curve with slop > 0). On the other hand the degradation of the polystyrene is mainly a random process in all its extension. The behaviour of each material used is related to its polydispersity and average molecular weight.
Chain scission level in the polymer degradation under multiple extrusions
Keywords: Polímeros; Degradação termomecânica; Múltiplas extrusões; Distribuição de massa molar; Cisão de cadeia; CSDF; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA